Chemical derivatization and biofunctionalization of hydrogel nanomembranes for potential biomedical and biosensor applications - Khan, Musammir; Schuster, Swen; Zharnikov, Michael (Physical chemistry, chemical physics, 2016)
Poly(ethylene glycol) based hydrogel nanomembranes (PHMs) are demonstrated to be able to host protein-specific receptors, providing, at the same time, stable, protein-repelling matrices with a characteristic mesh size up to 7-8 nm. The membranes were prepared by crosslinking of amino- and epoxy-terminated STAR-PEG precursors and maintained their hydrogel and protein-repelling properties even at a deviation of the precursor composition from the equilibrium value (1 : 1). The grafting density of the test avidin protein, specifically attached to the biotin moieties coupled to the free amine groups in the PHMs, varied from 0.45 × 1012 to 1.3 × 1012 proteins per cm2 within the sampling depth of the experiments (∼11.5 nm), depending on the precursor composition, whereas the analogous values for the non-specifically adsorbed proteins were lower by a factor of 4-5. The engineering of PHMs with biomolecule-specific receptors and their loading with biomolecules are of potential interest for sensor fabrication and biomedical applications, including tissue engineering and regenerative therapy.